Second Wave of COVID-19 Pandemic: Its deleterious and mortal repercussion in Pakistan - Rizwana Shahid; Shazia Zeb (Journal of Rawalpindi Medical College, 2020)
The detrimental consequences of Coronavirus infection are distinctly evident following its declaration as to the 6th Public Health Emergency of International Concern (PHEIC) by the World Health Organization on 30th January 2020 and its distressing and negative implications experienced across the globe. Apart from drastically impacting the healthcare of the population, a worrisome reduction in the universal economy is also attributed to this menace. The government of Pakistan is cognizant of its responsibilities took stringent measures to curb the coronavirus infection by the endowment of services for early case detection, contact tracing, isolation, and quarantine. Still, the first wave of COVID-19 resulted in a distressing scenario with the fast growth of this havoc in addition to those experienced in the United States, United Kingdom, Italy, and Spain. However, World Health Organization acknowledged the diligent efforts of the Pakistani government, healthcare professionals, and administrators in combating the first wave of COVID with an earlier reduction in effective Reproduction number (Rt) to 0.746 that was primarily attributed to Intermittent lockdown imposition, closure of educational institutes, avoidance of huge ceremonial gatherings and strict compliance to Standard Operating Procedures (SOPs). Although fewer chances of the second wave of COVID were anticipated in Pakistan due to early flattening of the curve during the first wave of COVID-19 in comparison with those of industrialized countries8 non-compliance to SOPs contributed to the rapid surge of the second wave. The government of Pakistan declared the occurrence of the second wave of COVID on 28th October 2020 when around 750 cases per day were reported. Active cases rapidly escalated to 11,000 and approximately 93 hospitalized patients were put on ventilators. Commencement of anti-government rallies and non-compliance to health guidelines are key contributors to this havoc. Currently, about 3499 active cases on daily basis are registered across the country with 39 deaths. About 410,000 active cases are detected nationally till now with 8260 fatalities. National Command and Operation Centre has accounted for a threefold ascend of infection since 12th October 2020. The steep ascend of cases during the second wave compelled the authorities to proceed with the shutting of learning institutes, the commencement of online education, and the postponement of all types of scheduled assessments except entrance exams. Even the employees of public and private sector medical institutes were vigilantly instructed to come to their offices on alternate days and keep working at home during the rest of the days from 25th November 2020 to 31st January 2021. Although these recommendations and initiatives by the concerned authorities can be of great assistance to curb the COVID pandemic but remaining extra cautious and strict observance of SOPs is of paramount significance to halt the rapid transmissibility of COVID. Stringent efforts of Rawalpindi Medical University-affiliated hospitals in battling the second wave of COVID are worth mentioning. Apart from Holy Family Hospital and Benazir Bhutto Hospital working to treat their respective catchment population, Rawalpindi Institute of Urology / Corona Hospital was reopened to cope up with the patient load amid the COVID pandemic. An adequate number of beds and necessary equipment were made available to manage the emerging infected cases.